Respuesta :
Answer:
[tex]x=\frac{-5-\sqrt{57} }{2}\ or\ x=\frac{-5+\sqrt{57} }{2}[/tex]
Step-by-step explanation:
Given:
The equation to solve is given as:
[tex]x^2=-5x+8[/tex]
Rearrange the given equation in standard form [tex]ax^2+bx +c =0[/tex], where, [tex]a,\ b,\ and\ c[/tex] are constants.
Therefore, we add [tex]5x-8[/tex] on both sides to get,
[tex]x^2+5x-8=0[/tex]
Here, [tex]a=1,b=5,c=-8[/tex]
The solution of the above equation is determined using the quadratic formula which is given as:
[tex]x=\frac{-b\pm \sqrt{b^2-4ac}}{2a}[/tex]
Plug in [tex]a=1,b=5,c=-8[/tex] and solve for [tex]x[/tex].
[tex]x=\frac{-5\pm \sqrt{5^2-4(1)(-8)}}{2(1)}\\x=\frac{-5\pm \sqrt{25+32}}{2}\\x=\frac{-5\pm \sqrt{57}}{2}\\\\\\\therefore x=\frac{-5-\sqrt{57} }{2}\ or\ x=\frac{-5+\sqrt{57} }{2}[/tex]
Therefore, the solutions are:
[tex]x=\frac{-5-\sqrt{57} }{2}\ or\ x=\frac{-5+\sqrt{57} }{2}[/tex]
Answer:
B is your answer!
Step-by-step explanation:
I just did it and got it correct
![Ver imagen BubblyGirly](https://us-static.z-dn.net/files/d17/89a1ed8024d597dc1bf57f317e7a02a0.png)